2018
DOI: 10.1186/s13638-018-1135-0
|View full text |Cite
|
Sign up to set email alerts
|

Ensemble learning particle swarm optimization for real-time UWB indoor localization

Abstract: This paper presents an ensemble learning particle swarm optimization (ELPSO) algorithm for real-time indoor localization based on ultra-wideband (UWB). Indoor localization problem can be formulated as an optimization problem to predict the target. The proposed algorithm expands the original PSO into ELPSO under superbest guide, which is a parameter employed to identify the top gbest by learning from three individual algorithms and updated asynchronously. The performance of the proposed ELPSO is evaluated by us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 47 publications
0
13
0
Order By: Relevance
“…Then we use the Lagrange duality method to solve the convex problem. Lastly, we find the parameters w, w 0 that minimizes w by (5). arg min w,w 0…”
Section: Fuse Learning Methods 1) Svm Model For the Nlos And Los Cmentioning
confidence: 99%
“…Then we use the Lagrange duality method to solve the convex problem. Lastly, we find the parameters w, w 0 that minimizes w by (5). arg min w,w 0…”
Section: Fuse Learning Methods 1) Svm Model For the Nlos And Los Cmentioning
confidence: 99%
“…In order to overcome the malfunctions in GPS positioning and to perform accurate positioning in a sophisticated indoor environment, systems called Indoor Positioning Systems (IPSs) are introduced. Some of the most popular technologies of this type are the infrared connection, WI-FI and above all Wi-Fi fingerprinting, which is often employed in the development of smart phone applications [2,3,4], Bluetooth, ZigBee, ultrasound, radio frequency identification (RFID), and ultra-wideband (UWB) [5,6], which offers higher accuracy.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Duru et al [5] investigated position-measuring algorithms for tracking an object with UWB sensors. Cai et al [4] developed an ensemble learning particle swarm optimization algorithm for indoor target detection and showed that it almost correctly detected target positions in empty indoor environment Although their method may be useful to identify each tag position, it is not evaluated for environment with Non-Line-of-Sight condition and multi-path problem yet, and the purpose of the algorithm is not to detect the stay regions of the target. Alhadhrami et al [1] used a UWB positioning system to develop a voice-guide service for a blind person.…”
Section: Introductionmentioning
confidence: 99%